Therapeutic efficacy of AAV8-mediated intrastriatal delivery of human cerebral dopamine neurotrophic factor in 6-OHDA-induced parkinsonian rat models with different disease progression. - Lizheng Wang; Zixuan Wang; Rui Zhu; Jinpeng Bi; Xinyao Feng; Wenmo Liu; Jiaxin Wu; Haihong Zhang; Hui Wu; Wei Kong; Bin Yu; Xianghui Yu (PLoS ONE)
Parkinson's disease (PD) is a progressive and age-associated neurodegenerative disorder. Patients at different stages of the disease course have distinguished features, mainly in the number of dopaminergic neurons. Cerebral dopamine neurotrophic factor (CDNF) is a recently discovered neurotrophic factor, being deemed as a hopeful candidate for PD treatment. Here, we evaluated the efficacy of CDNF in protecting dopaminergic function using the 6-OHDA-induced PD rat model suffering from different levels of neuronal loss and the recombinant adeno-associated virus 8 (AAV8) as a carrier for the CDNF gene. The results showed that AAV8-CDNF administration significantly improved the motor function and increased the tyrosine hydroxylase (TH) levels in PD rats with mild lesions (2 weeks post lesion), but it had limited therapeutic effects in rats with severe lesions (5 weeks post lesion). To better improve the recovery of motor function in severely lesioned PD rats, we employed a strategy using the CDNF gene along with the aromatic amino acid decarboxylase (AADC) gene. This combination therapeutic strategy indeed showed an enhanced benefit in restoring the motor function of severely lesioned PD rats by providing the neuroprotective effect of CDNF and dopamine enhancing effect of AADC as expected. This study may provide a basis for future clinical application of CDNF in PD patients at different stages and offer a new alternative strategy of joint use of CDNF and AADC for advanced PD patients in clinical trials.